The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0229380
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem vs standard of care for treatment of neonatal late onset sepsis (NeoMero1): A randomised controlled trial

Abstract: BackgroundThe early use of broad-spectrum antibiotics remains the cornerstone for the treatment of neonatal late onset sepsis (LOS). However, which antibiotics should be used is still debatable, as relevant studies were conducted more than 20 years ago, recruited in single centres or countries, evaluated antibiotics not in clinical use anymore and had variable inclusion/ exclusion criteria and outcome measures. Moreover, antibiotic-resistant bacteria have become a major problem in many countries worldwide. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
(49 reference statements)
0
30
0
Order By: Relevance
“…Overall, 87 infants from six European countries (the United Kingdom: 49, Estonia: 21, Greece: 7, Italy: 7, Lithuania: 2, Spain: 1) between 2010-2015 fulfilled our inclusion criteria and were included in the study. Forty patients were retrieved from the neonatal infection surveillance network (NeonIN) study [30], 38 from NeoMero [31], and 9 from the Collaborations for Leadership in Applied Health Research and Care (CLAHRC) study [32]. Patients, pathogens and treatment characteristics of the included episodes are summarised in Table 2.…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 87 infants from six European countries (the United Kingdom: 49, Estonia: 21, Greece: 7, Italy: 7, Lithuania: 2, Spain: 1) between 2010-2015 fulfilled our inclusion criteria and were included in the study. Forty patients were retrieved from the neonatal infection surveillance network (NeonIN) study [30], 38 from NeoMero [31], and 9 from the Collaborations for Leadership in Applied Health Research and Care (CLAHRC) study [32]. Patients, pathogens and treatment characteristics of the included episodes are summarised in Table 2.…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
“…A case series of neonates with clinical sepsis and microbiologically confirmed GN-BSIs was constructed from three separate studies: the NeonIN [30], the NeoMero clinical trial [31], and the CLAHRC [32]. The NeonIN is a multinational network which prospectively collect data on neonatal infections from neonatal units.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…Neonates with LOS were identified in 21 hospitals across Europe as previously described as part of the NeoMero studies. 1 21 The details of Neomero1 are presented elsewhere 22 . The recruitment centers were in 6 different countries (Italy, Greece, Estonia, Spain, Lithuania, and UK), and local ethics committees provided approval.…”
Section: Data Sourcementioning
confidence: 99%
“…In a very small study using an opportunistic sampling strategy with 9 cerebrospinal fluid (CSF) samples in 6 patients, CSF penetration of meropenem was estimated [24]. More recently, two large studies on meropenem use in neonates (NeoMero1 and NeoMero2) supported by the European Funded Program 7 reported on plasma and CSF PK of meropenem in neonates and young infants [27,28]. This much larger study collected 78 CSF samples in 56 patients and demonstrated that CSF penetration was low (8%).…”
Section: Meropenemmentioning
confidence: 99%